Management of unstable angina at rest by verapamil. A double-blind cross-over study in coronary care unit. Issue 2 (February 1979) - Parodi, O; Maseri, A; Simonetti, I
Abstract : A therapeutic trial with verapamil, a calcium-antagonist drug, was performed in 12 patients admitted to our coronary care unit because of frequent daily attacks of angina at rest attributed to coronary vasospasm. After a 48-hour run-in period, oral verapamil 480 mg/day and placebo were administered alternately during 4 randomised 48-hour periods. Transient ischaemic attacks with ST segment elevation or depression, with or without pain, were documented by continuous electrocardiographic monitoring. The number of attacks during the run-in and 2 placebo periods were 128, 123, and 130, respectively, and 31 and 23 during the 2 treatment periods (P less than 0.006 and P less than 0.003). This drug therefore appears to be effective in the management of patients with frequent attacks of angina at rest.